2018
DOI: 10.3332/ecancer.2018.859
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer patients have the highest malignancy-associated suicide rate in USA: a population-based analysis

Abstract: PurposePrevious studies have reported that psychological and social distresses associated with a cancer diagnosis have led to an increase in suicides compared to the general population. We sought to explore lung cancer-associated suicide rates in a large national database compared to the general population, and to the three most prevalent non-skin cancers [breast, prostate and colorectal cancer (CRC)].MethodsThe Surveillance, Epidemiology and End Results (SEER) database (1973–2013) was retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 30 publications
4
31
2
2
Order By: Relevance
“…Suicide rates have been shown to be higher in people with conditions associated with chronic pain or poor prognosis , including patients with cancer , neurological diseases such as amyotrophic lateral sclerosis or progressive multiple sclerosis . An analysis of the Surveillance, Epidemiology and End Results database 1973 to 2013 in the United States of America showed that SMRs for suicide ranged from 1.18 for prostate cancer to 4.17 for lung cancer . SMRs decreased over time for all cancers, but particularly for lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Suicide rates have been shown to be higher in people with conditions associated with chronic pain or poor prognosis , including patients with cancer , neurological diseases such as amyotrophic lateral sclerosis or progressive multiple sclerosis . An analysis of the Surveillance, Epidemiology and End Results database 1973 to 2013 in the United States of America showed that SMRs for suicide ranged from 1.18 for prostate cancer to 4.17 for lung cancer . SMRs decreased over time for all cancers, but particularly for lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Lung cancer is a malignant tumor with high morbidity and mortality [25]. Since the progress of traditional medical technology and the emergence of new treatment methods, such as targeted therapy and immunotherapy, the prognosis and five-year survival rate of various tumors are significantly improved [26].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the incidence rates of leukemia and suicide increased with the age of the patients, which is consistent with previous studies of elderly patients having other types of cancer. 22,33,34 The higher suicide rates of elderly leukemia patients might be related to their quality of life, outlook about life and death, and psychological condition such as the presence of depression. 11,35,36 Previous research has shown that the suicide rate among cancer patients in the United States is highest for whites and lowest for blacks.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that male sex, white race, marital status, and other risk factors are strongly correlated with the suicide rate of patients with certain types of cancer, such as kidney cancer, breast cancer, lung cancer, and head and neck cancer. 13,[20][21][22] Leukemia is a type of malignant proliferative disease involving hematopoietic stem cells. 23 There were 437,033 new leukemia patients identified worldwide in 2018, accounting for 2.4% of all new cancer patients and ranking 15th among new cancer patients.…”
Section: Introductionmentioning
confidence: 99%